Extradigital glomus tumour in the arm: A case report - Mohd Shaffid Md Shariff; Affirul Chairil; Razrim Rahim (Universiti Sains Islam Malaysia, 2024)
Journal of Surgery and Trauma Care, Vol. 1 No. 2 (2019) p. 1-3